Circulating Fibroblast Activation Protein as Potential Biomarker in Patients With Inflammatory Bowel Disease - Corsi, Fabio; Sorrentino, Luca; Albasini, Sara; Colombo, Francesco; Cigognini, Maria; Massari, Alessandro; Morasso, Carlo; Mazzucchelli, Serena; Piccotti, Francesca; Ardizzone, Sandro; Sampietro, Gianluca M.; Truffi, Marta (Frontiers in Medicine, 2021)
A major concern in the management of Inflammatory Bowel Disease (IBD) is the absence of accurate and specific biomarkers to drive diagnosis and monitor disease status timely and noninvasively. Fibroblast activation protein (FAP) represents a hallmark of IBD bowel strictures, being overexpressed in stenotic intestinal myofibroblasts. The present study aimed at evaluating the potential of circulating FAP (cFAP) as an accessible blood biomarker of IBD. Quantitative determination of cFAP was performed by enzyme-linked immunosorbent assay on plasma samples prospectively collected from patients with IBD and control subjects. A discrimination model was established on a training set of 50% patients and validated on independent samples. Results showed that cFAP concentration was reduced in patients with IBD when compared to controls (p<0.0001). Age, sex, smoking, disease location and behavior, disease duration and therapy were not associated with cFAP. The sensitivity and specificity of cFAP in discriminating IBD from controls were 70% and 84%, respectively, based on the optimal cutoff (57.6 ng mL-1, AUC=0.78). Predictions on the test set had 57% sensitivity, 65% specificity, and 61% accuracy. There was no strong correlation between cFAP and routine inflammatory markers in the patients’ population. A subgroup analysis was performed on patients with Crohn’s disease undergoing surgery and revealed that cFAP correlates with endoscopic mucosal healing. In conclusion, cFAP is significantly reduced in patients with IBD. Therefore, it deserves attention as a promising blood biomarker to triage patients with suspected IBD. Moreover, it might function as a biomarker of postoperative remission in patients with Crohn’s disease.